Fracture Toughness of Glass infiltrated (3Y-TZP/Al2O3) Composite - Sara N. Ibrahim; Shihab A. Zaidan; Mudhafar A. Mohammed (Engineering and Technology Journal, 2021)
Five different 3 mol.% yttria-tetragonal zirconia polycrystals/alumina (3Y-TZP/Al2O3) -glass specimens have been fabricated by the glass infiltration method. graphite additives were added to the (3Y-TZP/20Wt.%Al2O3) to obtain porous structure. The ATZ (Alumina Toughened Zirconia) skeleton have prepared by the normal compaction method. The specimen had been infiltrated by the glass (18Wt.% lithium hydroxide, 72 wt. % feldspar, and 10Wt.% nano Titanium oxide) at 1185ᵒC. Results showed that the porosity of (3Y-TZP/Al2O3) composite was increased while bulk density decreased with increasing graphite additives. The elastic modulus of (3Y-TZP/Al2O3)-glass was decreased (159-109GPa) with increasing the amount of glass infiltrated. Hardness was constant for all the specimens in value of (5.66 GPa), while increment of materials fracture toughening was due to the increasing the glass weight fraction, the kIc was lied between (0.53-1. 54MPa.m1/2). The glass infiltrated (3Y-TZP/Al2O3) process was successfully increased the fracture toughness by penetrated different amounts of glass into the (3Y-TZP/Al2O3) structure.